Microbiological and chemical characterization of fermented quinoa beverages obtained with kefir microorganisms - Pugliese, Andrea (2023)
Quinoa is an Andean pseudocereal considered a natural food resource of high nutritional value whose importance is recognized in food security for present and future generations. In this study we combined the nutritional power of quinoa with the potential beneficial effects of kefir. Microbiological and physico-chemical properties of fermented quinoa beverages with kefir grains, acid mother cultures thereof, or lactobacilli isolated from kefir, with reported potential probiotic effects, were evaluated. Fermented quinoa beverages obtained with Lactiplantibacillus plantarum CIDCA 83114 or acid mother cultures were comparable, although the Lb. plantarum strain demonstrated better growth at fermentation (to 8.63 ± 0.07 log CFU·ml-1 against 6.13 ± 0.07 log CFU·ml-1, respectively). Furthermore, the quinoa suspensions fermented with Lb. plantarum CIDCA 83114 showed more significant improvements on total phenolics, antioxidant activity, proteolysis and amylolytic activity than those fermented with acid mother cultures. In contrast, Lactobacillus kefiri CIDCA 8348 and kefir grains CIDCA AGK1 were not able to ferment the substrate. Kefir grains lost biomass integrity during repeated inoculations into quinoa suspensions and the viability of the lactic acid bacteria decreased. The present study revealed suitable characteristics of Lb. plantarum CIDCA 83114 as a starter to obtain nutritious and potentially health-promoting fermented quinoa beverages.